The Effect of Enterprise Risk Management (ERM) on the Soundness of Banking Companies in Indonesia - Handrawan, Merril Medelin; Rambe, Nadia Virginia; Harianto, Sandy; Wong, Daniel (Universitas Prasetiya Mulya, 2024)
This study examines whether ERM implementation is related to bank performance in Indonesian public banks. Using a sample of 32 public banks for the period of 2017-2021, this study found that ERM implementation are positively and significantly related to overall bank performance, as measured using CAMELS ratio. The results of this study support the argument using signalling and stakeholder theory, which states that banks show their commitment to the risk management process to their stakeholders through disclosure, so as to gain and maintain the trust of stakeholders, which can be reflected in bank performance. This study also found that some bank characteristics, namely age, leverage and share price volatility, have a negative and significant influence on bank performance. Furthermore, as an additional test, this study also found that there is a positive and significant effect of ERM implementation on bank performance during the Covid-19 pandemic period. Lastly, through sub-index analysis this study identifies that better risk organization has a positive and significant influence on bank performance.